A Technical Discourse: The Making of Pendhok Kris in Surakarta Style - Guntur; Milovan Sutrisno (Wacana Seni Journal of Arts Discourse, 2018)
The keris (kris) is a kind of Javanese dagger that has been recognised as a world cultural heritage of humanity by United Nations Educational, Scientific and Cultural Organization (UNESCO). The kris appears in various cultural events, including those of a ceremonial, ritual and sacred nature. It is believed that the possession of at least one kris is an indication of a person's "Javanese" identity. As an artefact, the kris, due to the prestige of its blade, sheath, hilt and pendhok, is a rare work of traditional art. The pendhok is the protective decorative plating on the sheath of the kris, which is usually made from various metals, such as silver, bronze, copper, brass, or even gold, and created by a craftsman known as a mranggi. A beautifully decorated pendhok may be more expensive than the blade itself. Despite an increase in discourse about the kris, there is still a lack of information about the pendhok. There are several forms of pendhok, which follow the two main styles of the sheaths of the Surakarta kris. The pendhok of the Surakarta kris has become a separate part of discourse on the subject of the Javanese kris, whereas in fact it has adapted according to the form of the kris promoted by changes in court policy. In the discourse on the subject of the Surakarta kris, the pendhok in its current form is in fact a material tradition, which displays a Javanese character born out of the relationship between the Dutch and the Javanese elite, as well as the relationship amongst the Javanese elite themselves in the history of colonialism. Taking this as a starting point, it is hoped that this description about the manufacturing of the pendhok in Surakarta style will enrich the existing discourse about the kris.